Intestinal Exposure to Ceftiofur and Cefquinome after Intramuscular Treatment and the Impact of Ceftiofur on the Pig Fecal Microbiome and Resistome - Sofie Rutjens; Nick Vereecke; Ward De Spiegelaere; Siska Croubels; Mathias Devreese (MDPI AG, 2022)
Optimization of antimicrobial treatment during a bacterial infection in livestock requires in-depth knowledge of the impact of antimicrobial therapy on the pathogen and commensal microbiota. Once administered antimicrobials and/or their metabolites are excreted either by the kidneys through urine and/or by the intestinal tract through feces, causing antimicrobial pressure and possibly the emergence of resistance in the gastro-intestinal tract. So far, the excretion of ceftiofur and cefquinome in the intestinal tract of pigs has not been described. The objective of this study was to investigate the excretion of ceftiofur and cefquinome in the different segments of the gut and feces after intramuscular administration. Therefore, 16 pigs were treated either with ceftiofur (n = 8) or cefquinome (n = 8), and feces were collected during the entire treatment period. The presence of ceftiofur and desfuroylceftiofuracetamide or cefquinome were quantified via liquid chromatography-tandem mass spectrometry. At the end of the treatment, pigs were euthanized, and samples from the duodenum, jejunum, ileum and cecum were analyzed. In feces, no active antimicrobial residues could be measured, except for one ceftiofur-treated pig. In the gut segments, the concentration of both antimicrobials increased from duodenum toward the ileum, with a maximum in the ileum (187.8 ± 101.7 ng·g−1 ceftiofur-related residues, 57.8 ± 37.5 ng·g−1 cefquinome) and sharply decreased in the cecum (below the limit of quantification for ceftiofur-related residues, 6.4 ± 4.2 ng·g−1 cefquinome). Additionally, long-read Nanopore sequencing and targeted quantitative polymerase chain reaction (qPCR) were performed in an attempt to clarify the discrepancy in fecal excretion of ceftiofur-related residues between pigs. In general, there was an increase in Prevotella, Bacteroides and Faecalibacterium and a decrease in Escherichia and Clostridium after ceftiofur administration (q-value < 0.05). The sequencing and qPCR could not provide an explanation for the unexpected excretion of ceftiofur-related residues in one pig out of eight. Overall, this study provides valuable information on the gut excretion of parenteral administered ceftiofur and cefquinome.